Persepsi Kelompok Tani Nelayan Segara Asih terhadap Pengembangan Wisata Bahari di Pantai Bias Munjul, Dusun Ceningan Kangin, Desa Lembongan, Kabupaten Klungkung - PUTRI, NI LUH MADE TARINA NANDA HARUM; PITANA, I GDE; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p38, 2023)
Perceptions of the Segara Asih Farmers and Fishermen Group on the Development of Marine Tourism at Bias Munjul Beach, Ceningan Kangin Hamlet, Lembongan Village, Klungkung Regency Nusa Ceningan with an area of 306 hectares has the potential as a place for tourism development, one of which is Munjul Bias marine tourism. Thus, this study aims to analyze perceptions and determine the factors supporting and inhibiting the development of marine tourism at Bias Munjul Beach, Lembongan Village. The research was conducted at Bias Munjul marine tourism from the end of April to July 2021. Data was collected through questionnaires and in-depth interviews. The data analysis used is a qualitative-quantitative descriptive analysis. The results showed that the overall level of perception could be categorized as "Strongly Agree". Then, the supporting factors for the development of Bias Munjul marine tourism are the tourist attractions, the availability of sea transportation, and the high participation of the community. Meanwhile, the biggest inhibiting factor is accessibility and government support. Suggestions that can be given are to immediately improve internal management, increase promotions, optimize facility maintenance, and immediately resolve road access problems, so as to support the development of Bias Munjul marine tourism in the future.